Design and Development of Google Sites-Based Interactive Learning Media for Wired and Wireless Network Technologies - Hanesa Putri Wulandari; Asrul Huda (Jurnal Vokasi Teknik Informatika, 2025)
The advancement of Information and Communication Technology (ICT) has significantly reshaped education, prompting the integration of technology-based learning media to improve instructional quality. Tools such as visual graphics, interactive texts, and educational videos enhance student comprehension and engagement. Google Sites, a free web-based platform, offers flexibility for delivering content across varied learning environments without requiring additional software. This study developed interactive learning media using Google Sites to support instruction in wired and wireless network technologies within vocational education. Employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research addressed the lack of interactive media and students' difficulties in grasping technical concepts. The resulting platform integrates texts, diagrams, video tutorials, and quizzes in a modular format suitable for both classroom and independent learning. Evaluation findings showed that 93% of students found the media easy to use, and 90% reported improved understanding. The study demonstrates a scalable approach to ICT-based learning and contributes to enhancing competency-based instruction in vocational contexts with limited infrastructure.